3D-Printed Gastroretentive Tablets Loaded with Niclosamide Nanocrystals by the Melting Solidification Printing Process (MESO-PP) - Juan Pablo Real; Daniel Andrés Real; Lucía Lopez-Vidal; Bruno Andrés Barrientos; Karen Bolaños; Mariano Guillermo Tinti; Nicolás Javier Litterio; Marcelo Javier Kogan; Santiago Daniel Palma (MDPI AG, 2023)
Niclosamide (NICLO) is a recognized antiparasitic drug being repositioned for Helicobacter pylori. The present work aimed to formulate NICLO nanocrystals (NICLO-NCRs) to produce a higher dissolution rate of the active ingredient and to incorporate these nanosystems into a floating solid dosage form to release them into the stomach slowly. For this purpose, NICLO-NCRs were produced by wet-milling and included in a floating Gelucire l3D printed tablet by semi-solid extrusion, applying the Melting solidification printing process (MESO-PP) methodology. The results obtained in TGA, DSC, XRD and FT-IR analysis showed no physicochemical interactions or modifications in the crystallinity of NICLO-NCR after inclusion in Gelucire 50/13 ink. This method allowed the incorporation of NICLO-NCRs in a concentration of up to 25% w/w. It achieved a controlled release of NCRs in a simulated gastric medium. Moreover, the presence of NICLO-NCRs after redispersion of the printlets was observed by STEM. Additionally, no effects on the cell viability of the NCRs were demonstrated in the GES-1 cell line. Finally, gastroretention was demonstrated for 180 min in dogs. These findings show the potential of the MESO-PP technique in obtaining slow-release gastro-retentive oral solid dosage forms loaded with nanocrystals of a poorly soluble drug, an ideal system for treating gastric pathologies such as H. pylori.